PHYSICAL, PHYSIOLOGICAL DEMANDS AND MOVEMENT PROFILES OF PROFESSIONAL MEN’S FIELD HOCKEY GAMES (Kinesiology, 2023)
The aim of this study was to investigate physical demands, physiological demands, and movement profiles of different positions across four quarters in professional men’s field hockey games. Eighteen professional male field hockey players participated in the study, and data were collected in eleven official matches. Players wore global positioning system units and heart rate monitors to collect physical, physiological, and movement profile data. Defenders had significantly higher absolute total distance covered, player load, acceleration and deceleration count, and forward-backward initial movement analysis (IMA) count, but lower high speed running distance, compared with midfielders and forwards (p